2007
DOI: 10.1002/bit.21760
|View full text |Cite
|
Sign up to set email alerts
|

Effect of electric currents on bacterial detachment and inactivation

Abstract: Since biofilms show strong resistance to conventional disinfectants and antimicrobials, control of initial bacterial adhesion is generally accepted as one of the most effective strategies for preventing biofilm formation. Although electrical methods have been widely studied, the specific properties of cathodic, anodic, and block currents that influence the bacterial detachment and inactivation remained largely unclear. This study investigated the specific role of electric currents in the detachment and inactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(147 citation statements)
references
References 23 publications
5
142
0
Order By: Relevance
“…With regard to the electrochemical mechanism of biofouling reduction, the influence of an electric current or potential on bacterial adhesion (12), detachment (10,(13)(14)(15), and inactivation (15)(16)(17) has been widely examined. The most commonly accepted theories are that the cathode repels bacteria via electrostatic interactions and the anode inactivates bacteria through direct and indirect oxidation (4,18).…”
mentioning
confidence: 99%
“…With regard to the electrochemical mechanism of biofouling reduction, the influence of an electric current or potential on bacterial adhesion (12), detachment (10,(13)(14)(15), and inactivation (15)(16)(17) has been widely examined. The most commonly accepted theories are that the cathode repels bacteria via electrostatic interactions and the anode inactivates bacteria through direct and indirect oxidation (4,18).…”
mentioning
confidence: 99%
“…Polymer brush coatings are monolayer coatings of modified polymer chains that have been shown to prevent bacterial adhesion to coated surfaces (33)(34)(35). The application of low-intensity electrical currents to electrically conductive implants has also been shown to decrease bacterial colonization (16,22,(52)(53)(54)(55). Similarly, the application of low-energy surface acoustic waves to urinary catheters prevented bacterial colonization in an animal infection model (18).…”
mentioning
confidence: 99%
“…116 As well, in a past study, Hong et al showed that a constant low current applied at a voltage well above the electrolysis threshold of water could remove up to 80% of the adherent biofilm from a conductive material after 20 minutes of treatment time. 120 The results from our study show a comparable reduction in biofilm activity, but using ultralow voltage and lower current, and in a shorter time.…”
Section: Discussionsupporting
confidence: 64%
“…113 A constant low current applied at a voltage well above the electrolysis threshold of water has been shown to remove up to 80% of the adherent biofilm from a conductive material after 20 minutes of treatment time. 120 It is also known that a low electrical current flow (1.5-10 mA) through titanium is able to enhance the antibacterial effects of chlorhexidine. 121 AlHashedi et al applied a current of 2.3 mA for 5 minutes at 1.8V and showed a reduction in bacterial viability and in the number of attached bacteria on an implant.…”
Section: The Bioelectric Effectmentioning
confidence: 99%